Magnetism in a helicate complexes arising with the tetradentate ligand. Issue 2 (24th December 2020) - Ohmagari, Hitomi; Nakaya, Manabu; Tanaka, Kaisei; Zenno, Hikaru; Akiyoshi, Ryohei; Sekine, Yoshihiro; Zhang, Yingjie; Min, Kil Sik; Hasegawa, Miki; Lindoy, Leonard F.; Hayami, Shinya
Abstract : The synthesis of [M(dimphen)(NCS)2 ] (M II = Fe (1 ), Co (2 ), Mn (3 )) and [Fe(dimphen)(NCSe)2 ] (4 ), where dimphen = [1, 2-bis(9-methyl-1, 10-phenanthrolin-2-yl)ethane], are reported. 1 shows ferromagnetic interaction, and 2 displays single-molecular magnet behaviour. Abstract : The synthesis of [M(dimphen)(NCS)2 ] (1 ; M = Fe II ), (2 ; M = Co II ), (3 ; M = Mn II ) and [Fe(dimphen)(NCSe)2 ] (4 ), where dimphen = [1, 2-bis(9-methyl-1, 10-phenanthrolin-2-yl)ethane], are reported. The crystal packing structures of 1–3, show intermolecular π–π stacking and NCS⋯SCN interactions. The complex 1 shows ferromagnetic interaction, and the complex 2 displays single-molecular magnet behaviour.